Cold Air Outbreaks Promote New Particle Formation Off the U.S. East Coast. Issue 5 (2nd March 2022) - Corral, Andrea F.; Choi, Yonghoon; Crosbie, Ewan; Dadashazar, Hossein; DiGangi, Joshua P.; Diskin, Glenn S.; Fenn, Marta; Harper, David B.; Kirschler, Simon; Liu, Hongyu; Moore, Richard H.; Nowak, John B.; et al.
Abstract: New particle formation (NPF) is the dominant contributor to total particle number concentration and plays an important role in the cloud condensation nuclei budget. Airborne data from Aerosol Cloud meTeorology Interactions oVer the western ATlantic Experiment (ACTIVATE) are used to address seasonal NPF statistics and factors related to NPF in and around clouds. Higher ratios of particle concentrations greater than 3 versus 10 nm (N3 /N10 ) were mainly observed above boundary layer cloud tops during winter as compared to summer. Cold dry air and low aerosol surface area concentration facilitate NPF over the ACTIVATE region; these conditions are especially prevalent during flights coinciding with cold air outbreaks. Plain Language Summary: Airborne data collected during the Aerosol Cloud meTeorology Interactions oVer the western ATlantic Experiment (ACTIVATE) campaign's first year of research flights during the winter (February 14 to March 12, 2020) and summer (August 13 to September 30, 2020) provide insight on new particle formation over the Western North Atlantic Ocean. The formation of new particles in the atmosphere is the primary contributor to total particle number concentration and plays a key role in the cloud condensation nuclei budget. Airborne observations reveal more active new particle formation during the winter than summer, especially just above boundary layer cloud tops. Influential conditions coinciding with new particle formation include cold and dry air, along with low aerosol surface area concentration and high levels of precursor gases from continental outflow. These conditions are shown to be most prevalent during cold air outbreaks in the winter off the United States East Coast. Key Points: New particle formation is more prevalent off the U.S. East Coast in winter rather than summer Ratio of particle number above 3 versus 10 nm peaks above cloud top regardless of season Cold and dry conditions during cold air outbreaks coincide with new particle formation